Magnetic Resonance Imaging in Multiple Sclerosis: An Analysis of the Implementation of the Portuguese Consensus - Ricardo Soares dos Reis; Alyne Cordeiro; Ana João Marques; Ana Rita Castro; Cristiana Silva; Duarte Carapinha; Francisca Ferreira; Miguel Schön; Daniela Jardim Pereira; João Paulo Gabriel; Luís Ruano; Mariana Santos; et al. (Acta Médica Portuguesa, 2025)
Introduction: Magnetic resonance imaging (MRI) plays a critical role in diagnosing and monitoring people with multiple sclerosis (MS). The 2020 Portuguese Consensus on Magnetic Resonance Imaging in Multiple Sclerosis aimed to standardize MRI use. This study evaluated the implementation of the consensus in clinical practice.